2022
DOI: 10.1177/00953997221131790
|View full text |Cite
|
Sign up to set email alerts
|

Individual, Group, and Collective Co-production: The Role of Public Value Conceptions in Shaping Co-production Practices

Abstract: In this paper, I explore how different conceptions of public value influence the types of co-production that professionals undertake in delivering projects to reduce loneliness and isolation of older people. The analysis shows a preponderance of individual and group co-production by the case in England, driven by aims to create user and group value, whereas the French case emphasizes collective co-production linked to social and political value. The research contributes to the co-production literature by showi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 46 publications
(61 reference statements)
0
2
0
Order By: Relevance
“…The health and welfare system is not exempt from the need to transform and improve services, and co-creation has emerged as a potential solution to address the various challenges faced (Acar et al, 2023 ; McMullin, 2023 ; Torfing et al, 2023 ). The focus on co-creation in recent years has also influenced innovations in the health and welfare services and the creation of public values (Acar et al, 2023 ; Palumbo, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The health and welfare system is not exempt from the need to transform and improve services, and co-creation has emerged as a potential solution to address the various challenges faced (Acar et al, 2023 ; McMullin, 2023 ; Torfing et al, 2023 ). The focus on co-creation in recent years has also influenced innovations in the health and welfare services and the creation of public values (Acar et al, 2023 ; Palumbo, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that implementing research-based knowledge into health services takes many years and pointed to several difficulties in this regard (Gabbay & le May, 2023 ; Graham et al, 2006 ; Khan et al, 2021 ; Morris et al, 2011 ; Straus et al, 2013 ). These include problems relating to the integration of professional perspectives anchored within a bio-medical model with lay actors’ knowledge derived from a democratic and emancipatory tradition (McMullin, 2023 ; Palumbo, 2016 ; Torfing et al, 2023 ). Professionals also need to change their roles from acting as providers of services to managing collaborative service provision processes (Steen et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%